Boronate-Based Probes for Biological Oxidants: A Novel Class of Molecular Tools for Redox Biology - Sikora, Adam; Zielonka, Jacek; Dębowska, Karolina; Michalski, Radosław; Smulik-Izydorczyk, Renata; Pięta, Jakub; Podsiadły, Radosław; Artelska, Angelika; Pierzchała, Karolina; Kalyanaraman, Balaraman (Frontiers in Chemistry, 2020)
Boronate-based molecular probes are emerging as one of the most effective tools for detection and quantitation of peroxynitrite and hydroperoxides. This review discusses the chemical reactivity of boronate compounds in the context of their use for detection of biological oxidants, and presents examples of the practical use of those probes in selected chemical, enzymatic, and biological systems. The particular reactivity of boronates toward nucleophilic oxidants makes them a distinct class of probes for redox biology studies. We focus on the recent progress in the design and application of boronate-based probes in redox studies and perspectives for further developments.